Nanog Signaling Mediates Radioresistance in ALDH-Positive Breast Cancer Cells - Dehghan Harati, Mozhgan; Rodemann, H. Peter; Toulany, Mahmoud (International journal of molecular sciences, 2019)
Recently, cancer stem cells (CSCs) have been identified as the major cause of both chemotherapy and radiotherapy resistance. Evidence from experimental studies applying both in vitro and in vivo preclinical models suggests that CSCs survive after conventional therapy protocols. Several mechanisms are proposed to be involved in CSC resistance to radiotherapy. Among them, stimulated DNA double-strand break (DSB) repair capacity in association with aldehyde dehydrogenase (ALDH) activity seems to be the most prominent mechanism. However, thus far, the pathway through which ALDH activity stimulates DSB repair is not known. Therefore, in the present study, we investigated the underlying signaling pathway by which ALDH activity stimulates DSB repair and can lead to radioresistance of breast cancer cell lines in vitro. When compared with ALDH-negative cells, ALDH-positive cells presented significantly enhanced cell survival after radiation exposure. This enhanced cell survival was associated with stimulated Nanog, BMI1 and Notch1 protein expression, as well as stimulated Akt activity. By applying overexpression and knockdown approaches, we clearly demonstrated that Nanog expression is associated with enhanced ALDH activity and cellular radioresistance, as well as stimulated DSB repair. Akt and Notch1 targeting abrogated the Nanog-mediated radioresistance and stimulated ALDH activity. Overall, we demonstrate that Nanog signaling induces tumor cell radioresistance and stimulates ALDH activity, most likely through activation of the Notch1 and Akt pathways.